Influence of probiotics and deoxycholate on azathioprine transport in the PAMPA model: insights into pharmacomicrobiomics and interindividual variability in drug response - Đanić, Maja; Pavlović, Nebojša; Dedić, Natalija; Zaklan, Dragana; Lazarević, Slavica; Stanimirov, Bojan; Mikov, Momir (Frontiers in Pharmacology, 2025)
IntroductionInterindividual variability in drug response presents a major clinical challenge, necessitating a deeper understanding of contributing factors. While the role of gut microbiota, probiotics and bile acids in modulating drug metabolism, absorption, and bioavailability is increasingly recognized, their precise impact on variability remains an active area of research. Azathioprine, a widely used immunosuppressant for inflammatory bowel disease, exhibits significant variability in patient response. This study investigates the effects of probiotic bacteria and sodium deoxycholate (DC) on azathioprine permeability to elucidate mechanisms underlying interindividual differences in drug absorption and therapeutic outcomes.MethodsThe parallel artificial membrane permeability assay (PAMPA) was used to evaluate the permeability of azathioprine at pH 5.8, 6.5, and 7.4, both alone and in combination with DC and probiotics. Following a six-hour incubation, azathioprine concentrations were quantified using high-performance liquid chromatography (HPLC), and permeability coefficients were calculated. Additionally, molecular mechanics (MM2) calculations were performed to analyze interactions between azathioprine and bile acids. Chemoinformatics-based platforms, pkCSM and ADMETsar, were used to predict the interactions of azathioprine and DC with drug transporters in the gastrointestinal tract, particularly P-glycoprotein (P-gp).ResultsAzathioprine exhibited higher permeability at lower pH values. The presence of probiotic bacteria resulted in a statistically significant increase in azathioprine permeability; however, the total amount of azathioprine during incubation with bacteria significantly decreased. DC reduced drug permeability, with higher DC concentrations leading to a greater decrease in azathioprine permeability, as reflected by lower drug levels in the acceptor compartment, likely due to the formation of hydrophilic complexes with azathioprine, which exhibit lower membrane permeability compared to the free drug. In silico analysis suggested that azathioprine absorption may involve intestinal transport proteins, including P-gp, and that DC, as a P-gp inhibitor, could additionally affect its absorption and bioavailability through this mechanism.ConclusionThe findings indicate significant interactions between probiotic bacteria, DC, and azathioprine that may affect azathioprine absorption. Since the PAMPA method is exclusively suited for evaluating passive transport, additional in vitro and in vivo studies are required to further investigate the interactions of azathioprine with intestinal bacteria and bile acids, ultimately determining their impact on intestinal absorption and bioavailability.